Perancangan Flat Pack Furniture - Erwin Agustiano; Andereas Pandu Setiawan; Frenky Tanaya (Intra, 2018)
Furniture that is cheap, easy to send and does not require much space for delivery is the people’s first choice nowadays. Many people prefer to buy furniture from the store, then bring it home and install it by their selves once they arrive home. This kind of furniture is the new breakthrough in modern times. In addition to practical and easy to carry, flat pack furniture or knock-down furniture can also save shipping costs because it does not require a large space for the delivery process. Usually this furniture is neatly wrapped in a box made of cardboard. The manual book of how to install the furniture is also included in the furniture packaging. Furniture installation also does not require any tools.